Econometric Modelling of Antitrust Environment and Patent Activity - Marinova, Dora; Mcaleer, M.; Slottje, D. (Modelling and Simulation Society of Australia and New Zealand, 2005)
This paper examines the relationship between the antitrust environment and technological inventiveness in the US economy, where technological inventiveness is measured by patent activity. Although not all registered patents are commercialised into inventions, patent data provide a valuable source of information about technological efforts. Patenting is also very important as it is linked to an economic and legal environment which actively encourages and protects competition. The US economy has been providing legal protection to inventors for more than 200 years now, and in the last 100 years or more it has also been a relatively highly regulated antitrust environment. The hypothesis tested in the study is whether antitrust enforcement activity, as measured by the number of civil filings of the US Department of Justice, has had a significant impact on the level of technological inventiveness in the US economy, after adjusting for other factors that have an impact on innovation, such as research and development expenditures and real economic growth. Impacts of civil antitrust case filings, criminal antitrust case filings and total US Department of Justice antitrust case filings on patent activity in the USA (based on data from the US Patent and Trademark Office) are estimated for the period 1953-2000.During the above period, patent activity and R&D expenditure have exhibited increasing trends; while the growth rate in real GDP has not exhibited noticeable trending behaviour and unemployment rate peaked in the mid-1980s and subsequently declined in the 1990s. Criminal antitrust filings comprise 60% of total antitrust filings and they have not exhibited any discernible trends during the 1953-2000 period; while civil antitrust filings peaked in the early 1960s and early 1970s, then declined dramatically in the 1980s followed by a slight rise in the 1990s and gradual decline towards the end of the period. Against this background, the estimated econometric models assume that technological inventiveness (for which the proxy is patent activity) is a function of past patent activity, US aggregate R&D expenditures, the rate of growth in real GDP, the overall US unemployment rate and includes antitrust enforcement variables (civil, criminal and total antitrust filings). The estimation is undertaken by weighted least squares and the Newey-West heteroskedasticity and autocorrelation consistent method is used to adjust for possible heteroskedasticity and/or serial correlation. All the models are estimated using the EViews 4.0 econometric software package. A simple dynamic model that provided an adequate fit to the data is given as follows: Patent Successt = 20736 + 0.48 Patent Successt-1 + 0.24 US R&Dt + 643 Real GDP Growtht – 1991 US Unemployment Ratet + 308 Civil Antitrust Cases Filedt-1.The empirical results show that civil case filings have a statistically significant impact on technological inventiveness. Residual claimants of firms clearly understand the competitive landscape of the US economy in which they operate – when the US Department of Justice emits a signal to the market of robust enforcement intent, firms react by increasing their technological inventiveness. It might also be expected that civil antitrust filings would have a stronger impact than criminal antitrust activity on innovative activity as the civil cases involve firms that play according to legal rules.